Magic - Wiseman, Richard (Arts for health., 2023)
Extraordinary feats of conjuring have long entertained and astounded audiences. However, few people realise that magic also has the power to improve health and to enhance wellbeing. Join magician, author, and psychologist Richard Wiseman as he journeys into this secretive world and uncovers the surprising therapeutic and educational benefits of making the impossible possible. Written for both performers and practitioners, this comprehensive but accessible guide describes the many ways in which watching and learning magic helps people. Discover how hospital magicians promote the recovery of patients, how occupational therapists teach tricks that boost movement and coordination, how counsellors conjure up life skills, and how illusions enhance curiosity and learning in the classroom. Along the way, Wiseman reveals some of the amazing but simple tricks of the trade, presents key initiatives from around the world, explores academic research examining the efficacy of magic-based interventions, and interviews experienced practitioners carrying out this work. The first publication of its kind, Magic is essential reading for anyone who wishes to understand and utilise the real magic of magic.